Analisis pendapatan, pendidikan dan jumlah anggota keluarga terhadap pola konsumsi daging ayam broiler di Desa Sei Asam Kabupaten Kapuas - - Kastalani; - Yemima; Hendri Sularso (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
The study aims to determine the pattern of broiler chicken consumption and know the influence of income factor, education and number of family members to the pattern of broiler chicken meat consumption at Sei Asam village, Kapuas regency. The research was done by using survey method and direct interview to the field, data analysis technique with statistical test multiple linier. The results showed variable income, education and number of a family member simultaneously significantly influence consumption pattern of broiler chickens meat. The partial variable of income significantly influence the pattern of broiler chicken consumption, while the variable of education and number of family members do not give influence.